Antidiabetic Activity of the Alcoholic Extract of the Arial Part of Boerhaavia diffusa in Rats - Savita S1, Gnaneshwari D1, Bhatia V1*, Kinja K1, Bishnoi H1 (Recent Research in Science and Technology, 2011)
This study indicates that Boerhaavia diffusa alcoholic extracts have good antidiabetic activity. Methanolic and ethanolic extracts of Boerhaavia diffusa at a dose level of 200 mg/kg/p.o exhibited significant anti-hyperglycemic activities in alloxan induced as well as in streptazotocin induced hyperglycemic rats. They can also improve the condition of diabetes as indicated by parameters like body weight along with serum cholesterol and triglyceride levels. The extracts of the plant Boerhaavia diffusa was tested for oral hypoglycaemic and anti-diabetic activity, by glucose oral tolerance test, alloxan induced and streptozotocin induced diabetic rats respectively. The extracts of Boerhaavia diffusa have shown significant (P<0.001) increase in glucose tolerance, but methanolic extract shows more activity. In alloxan-induced diabetic rats also the maximum percentage reduction in blood glucose levels was found to be in Boerhaavia diffusa methanolic extract. Animals, which received STZ, also showed a significant reduction in body weight, and increase in water and food intake as compared to vehicle control, which is significantly reversed by methanolic extracts of Boerhaavia diffusa and after 21 days of treatment. These results indicate that the plant Boerhaavia diffusa possess significant anti – diabetic activity